Development in the Organization of Episodic Memories in Middle Childhood and Adolescence - Chen, Yan; McAnally, Helena M.; Reese, Elaine (Frontiers in Behavioral Neuroscience, 2013)
The basic elements of autobiographical or episodic memory are established in early childhood, although the exact age at which memories gain episodic status is still under contention. The self-memory system proposed that adults use “lifetime periods” to group episodic memories together into life story chapters. Two studies examined at what point in development children or adolescents begin to take advantage of lifetime-period chapters to organize their episodic memories. The results of Study 1 with 8- to 12-year-olds revealed that the ability to provide life story chapters began to emerge as early as 8 years of age. In Study 2 with adolescents aged 12 to 21, this ability continued to develop into late adolescence among New Zealand European and New Zealand Chinese adolescents; however, cultural differences also existed in the specificity of memories. New Zealand Chinese adolescents narrated fewer life story chapters containing specific memories than New Zealand European adolescents. These findings support and extend current theories of episodic memory by specifying that pre-adolescents are starting to organize their episodic memories into lifetime periods, but this achievement is not fully realized until later in adolescence.